Clinical Options in Relapsed or Refractory Hodgkin Lymphoma: An Updated Review. (16th December 2015) - Fedele, Roberta; Martino, Massimo; Recchia, Anna Grazia; Irrera, Giuseppe; Gentile, Massimo; Morabito, Fortunato
Abstract : Hodgkin lymphoma (HL) is a potentially curable lymphoma, and modern therapy is expected to successfully cure more than 80% of the patients. Second-line salvage high-dose chemotherapy and autologous stem cell transplantation (auto-SCT) have an established role in the management of refractory and relapsed HL, leading to long-lasting responses in approximately 50% of relapsed patients and a minority of refractory patients. Patients progressing after intensive treatments, such as auto-SCT, have a very poor outcome. Allogeneic SCT represents the only strategy with a curative potential for these patients; however, its role is controversial. Based on recent knowledge of HL pathology, biology, and immunology, antibody-drug conjugates targeting CD30, small molecule inhibitors of cell signaling, and antibodies that inhibit immune checkpoints are currently explored. This review will discuss the clinical results regarding auto-SCT and allo-SCT as well as the current role of emerging new treatment strategies.